Upaya Meningkatkan Motivasi Belajar Menggunakan Model Cooperative Learning dengan Media Video pada Pelajaran Bahasa Indonesia - ., Wahyuni; Triana, Dian (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2023)
After learning Indonesian sentences, it can be concluded that students are less focused on learning. When the researcher explained the material, some students were not interested in listening to the explanation. The purpose of this study was to determine the application of the Cooperative Learning learning model using video media to increase learning motivation. This Class Action Research was conducted in 2 cycles. Based on The test results obtained at the end of each cycle, shows that there is a significant increase in Indonesian learning outcomes. Starting from the pre-cycle, initially 22.22% achieved completeness or above the KKM, then in cycle, I there was an increase of 66.67%, and in cycle II there was an increase of 88.89% in fulfilling the KKM. So it can be concluded that the use of cooperative learning models with video media can increase student motivation.